Two new species of Phyllonema (Rivulariaceae, Cyanobacteria) with an emendation of the genus - González-Resendiz, Laura; Johansen, Jeffrey R; Escobar-Sánchez, Viviana; Segal-Kischinevzky, Claudia; Jiménez-García, Luis F; León-Tejera, Hilda (Journal of phycology, 2018)
Two untapered, heterocytous species were observed and collected from the intertidal and supratidal zones of the Mexican coastline of the Pacific Ocean near Oaxaca and from the Gulf of Mexico. These populations were highly similar in morphology to the freshwater taxon Petalonema incrustans in the Scytonemataceae. However, 16S rRNA sequence data and phylogenetic analysis indicated that they were sister taxa to the epiphyllic, Brazilian species Phyllonema aveceniicola in the Rivulariaceae, described from culture material. While genetic identity between the two new species was high, they differed significantly in morphology, 16S rRNA gene sequence identity, and sequence and structure of the 16S-23S ITS region. Their morphology differed markedly from the generitype of the previously monotypic Phyllonema, which has tapered, heteropolar, single-false branched trichomes with very thin or absent sheath. The two new species, Phyllonema ansata and Phyllonema tangolundensis, described from both culture and environmental material, have untapered, isopolar, geminately false branched trichomes with thick, lamellated sheaths, differences so significant that the species would not be placed in Phyllonema without molecular corroboration. The morphological differences are so significant that a formal emendation of the genus is required. These taxa provide a challenge to algal taxonomy because the morphological differences are such that one would logically conclude that they represent different genera, but the phylogenetic evidence for including them all in the same genus is conclusive. This conclusion is counter to the current trend in algal taxonomy in which taxa with minor morphological differences have been repeatedly placed in separate genera based primarily upon DNA sequence evidence.
Keywords: sekundární struktura proteinů; Oaxaca; DNA, Ribosomal Spacer; RNA, Ribosomal, 16S; Phyllonema; sekvenční analýza RNA; sinice; Mexiko; Mexico; Cyanobacteria; ITS secondary structure; Sequence Analysis, RNA; RNA řas; bílkoviny řas; Rivulariaceae; Algal Proteins; RNA ribozomální 16S; Protein Structure, Secondary; Scytonemataceae; fylogeneze; cyanobacteria; RNA, Algal; 16S-23S ITS; Phylogeny; mezerníky ribozomální DNA